2021
DOI: 10.1016/j.ebiom.2021.103538
|View full text |Cite
|
Sign up to set email alerts
|

Airway microbial communities, smoking and asthma in a general population sample

Abstract: Background Normal airway microbial communities play a central role in respiratory health but are poorly characterized. Cigarette smoking is the dominant global environmental influence on lung function, and asthma has become the most prevalent chronic respiratory disease worldwide. Both conditions have major microbial components that are incompletely defined. Methods We investigated airway bacterial communities in a general population sample of 529 Australian adults. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 64 publications
7
58
0
1
Order By: Relevance
“…The interactions among bacterial genera are extremely subtle. According to previous studies [ 30 , 31 ], the abundances of Prevotella and Veillonella significantly increase in the pulmonary microecology of patients with lung cancer and those with asthma [ 28 , 29 ]. This study found that Prevotella and Veillonella cooperated with each other and that Ochrobactrum and Rhodococcus were synergetic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions among bacterial genera are extremely subtle. According to previous studies [ 30 , 31 ], the abundances of Prevotella and Veillonella significantly increase in the pulmonary microecology of patients with lung cancer and those with asthma [ 28 , 29 ]. This study found that Prevotella and Veillonella cooperated with each other and that Ochrobactrum and Rhodococcus were synergetic.…”
Section: Discussionmentioning
confidence: 99%
“…The interrelations among the bacteria suggest a hypothesis: in addition to the use of drugs to suppress or kill pathogenic bacteria, it means to increase the abundance of the competitor of the pathogenic bacteria, such as bacterial transplantation and regulation of the intestinal flora, may also help enhance the treatment effect. Oral administration or transplantation of probiotics can improve pulmonary resistance against viruses, Mycobacterium tuberculosis , and other pathogenic bacteria [ 30 , 31 , 32 , 33 , 34 ]. Currently, broad- or ultrabroad-spectrum antibiotics have been used to target Pseudomonas aeruginosa in clinical practice [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of COPD has increased worldwide, and it is the principal cause of morbidity and mortality [ 2 ]. The common symptoms of the disease include dyspnoea, cough, sputum, and altered respiratory composition resulting from chronic exposure to cigarette smoke (CS) or pollutants [ 3 ]. In fact, CS affects the microbial composition mainly through lack of oxygen and increased formation of bacterial biofilms [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The common symptoms of the disease include dyspnoea, cough, sputum, and altered respiratory composition resulting from chronic exposure to cigarette smoke (CS) or pollutants [ 3 ]. In fact, CS affects the microbial composition mainly through lack of oxygen and increased formation of bacterial biofilms [ 3 , 4 ]. Inhalation of CS results in the activation of epithelial and immunomodulatory cells, including neutrophils, macrophages, and T cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation